Patterns of vespa velutina invasion in western Iberia and Italy as revealed by molecular markers - Quaresma, Andreia (2018)
The Yellow-legged or Asian hornet (Vespa velutina nigrithorax) was naturally distributed in Southeast Asia. However, in 2004, it was accidently introduced in France from China and in the last decade it spread rapidly through the French territory and to other European countries. In the Iberian Peninsula it was reported for the first time in Spain, in 2010, and in Portugal, in 2011. Using a population genetics framework, the goal of this study was to test the genetic patterns of colonization of this invasive honey bee predator in the Atlantic side of Iberia and in Italy. A total of 246 individuals, each representing a single colony, were collected across the invaded area in Portugal (190), Spain (45) and Italy (11). Additionally, a dataset containing samples from France, Vietnam, South Korea, Indonesia and two provinces of China provided by Arca et al. (2015) was used as a reference for testing hypothesis about origin of the invasion. The genetic variability was assessed using 16 microsatellite loci and the mitochondrial cytochrome C oxidase. Population structure was inferred using the Bayesian approach STRUCTURE and diversity was estimated using GenAlex 6.5. Our results show that genetic diversity is low in Portugal, as expected from a founder effect originating from the French population. The Spanish population shows a higher genetic diversity and our data suggest that this is due to independent invasions originating from two range expansions: one from France and another from Portugal. The molecular data obtained for the Italian sample show diversity levels similar to those of Spain and supports introduction by range expansion from France. The mtDNA analysis revealed the presence of a single haplotype in Iberia and Italy, which has been also reported for France and UK. These results are in accordance with other European studies, further supporting an entrance of a small number of propagules or even of a single multi-mated queen in Europe.